2018
DOI: 10.1002/jbm.b.34228
|View full text |Cite
|
Sign up to set email alerts
|

In situ transplantation of adipose tissue‐derived stem cells organized on porous polymer nanosheets for murine skin defects

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The nanosheet has strong physical adsorption via Van der Waals forces due to its thinness 23 . Hence, a nanosheet can be an excellent scaffold that carries ASCs onto the wound without the need for an adhesive agent 24 . Nishiwaki et al reported the wound healing effect of ASC transplantation with a tri-layered porous nanosheet.…”
Section: Introductionmentioning
confidence: 99%
“…The nanosheet has strong physical adsorption via Van der Waals forces due to its thinness 23 . Hence, a nanosheet can be an excellent scaffold that carries ASCs onto the wound without the need for an adhesive agent 24 . Nishiwaki et al reported the wound healing effect of ASC transplantation with a tri-layered porous nanosheet.…”
Section: Introductionmentioning
confidence: 99%
“…ECM proteins such as fibronectin, collagen and laminin penetrate through the micropores to stabilize cell hierarchies constructed between multi-layered porous nanosheets. Additionally, it has been reported that porous nanosheets facilitated long-term cell culture (up to 2 weeks) with more than 80% cell viability and oriented cell arrangement ( Nishiwaki et al, 2019 ). Most recently, we reported for the first time that porous nanosheets prepared by a solvent etching method could support the adipose-tissue derived stem cell (ASC) spheroids for high-magnification imaging owing to its transparency ( Suematsu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated the transplantation of ASCs using this multilayered porous nanosheet and showed promotion of the wound healing effects against skin defects 27 . However, considering the spatial limitation of the nanosheet for loading ASCs on its surface, this approach transplanting 2D adhesive cells is insufficient for secreting sufficient growth factors to induce angiogenesis for the treatment of skin ulcers.…”
Section: Introductionmentioning
confidence: 99%